Faktor-Faktor yang Memengaruhi Proses Keputusan Pembelian Daging Sapi Beku di Kelurahan Pagerwojo, Kecamatan Buduran, Kabupaten Sidoarjo, Jawa Timur: Studi Kasus OpheliaMart - Salma, Ophelia; Azizah, Siti (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Meat is a food ingredient that is popular with consumers in Indonesia. However, if fresh meat is not immediately processed further, it will damage its physical quality and nutritional quality. This encourages producers of processed livestock food to carry out product innovations in the form of frozen processed products, such as frozen meat. This study aims to identify the characteristics of consumers purchasing frozen meat and the factors that influence their decision-making process. The study surveyed 30 OpheliaMart consumers in the Pagerwojo Village area, Buduran District, Sidoarjo Regency, East Java Province, using judgmental sampling techniques from 10th February – 10th March 2024. Primary data was taken from interviews by respondents with the help of a likert scale questionnaire. Then, primary data was tested using research instrument tests, classical assumption tests, multiple linear regression analysis tests, and hypothesis tests assisted using IBM statistical package for the social science (SPSS) version 25 software. The characteristics of consumers who buy frozen meat mostly include females aged 40 – 50 with the majority being housewives and having a monthly income exceeding IDR 5 million. On average, consumers purchased 1 – 3 kilogram of frozen meat per month. The decision-making process for purchasing frozen meat is influenced by personal, psychological, social, and cultural factors. The study found that while personal and psychological factors do not significantly influence the decision-making process, but social and cultural factors play a significant role.